A report on the Human Computation Workshop (HComp 2009) - Ipeirotis, Panos G.; Chandrasekar, Ramen; Bennett, Paul; Law, Edith; Chickering, Max; Mityagin, Anton; Provost, Foster; Ahn, Luis von (KDD Explorations, 2009)
The first Human Computation Workshop (HComp2009) was held on June 28th, 2009, in Paris, France, collocated with SIGKDD 2009. This report summarizes the workshop, with details of the papers, demos and posters presented. The report also includes common themes, issues, and open questions that came up in the workshop.